Working Conditions and Health of Recyclable Material Collectors During the COVID-19 Pandemic - Almeida, Ana Paula; Crovador, Cleyton Cristiano; Barcia, Maiza Karine; Veiga, Tatiane Bonametti (National Journal of City Management, 2024)
Recyclable material collectors belong to a professional category frequently exposed to various risks associated with working conditions in waste management. This study aimed to identify the working conditions and health of collectors in the municipality of Ponta Grossa-PR during the COVID-19 pandemic. The research utilized a sample composed of 83 associated collectors. Among the findings, it was identified that the majority of collectors were female (72.3%). The professional profile demonstrated that collectors engaged in this work out of necessity (34.0%) and because it was the only opportunity available (26.0%). Regarding health and occupational risks during the pandemic, it was found that although the collectors had developed protective strategies to avoid COVID-19 infection (94.0%), nearly half of the workers (47.0%) had contact with potentially infectious waste. During this period, activities were suspended only for those of advanced age (16.9%). Concerning COVID-19 cases, 98.8% of participants reported not having contracted the disease, but this result does not dismiss the fact that the collectors were exposed to contagion risks. From this diagnosis, it was possible to conclude that the COVID-19 pandemic caused various changes in the lives of the collectors, revealing the need for the development of emergency preventive actions for the health of these workers. For this reason, it is suggested that studies continue to guide the development of strategies that can be adopted in other widespread epidemic situations, similar to those experienced during the COVID-19 period.